Engaged Learning: Primary Teachers’ Beliefs and Performance-Related Self-Perception - Pipere, Anita (Acta Paedagogica Vilnensia, 2005)
The research extends the knowledge on relationships between the teachers’ beliefs and performance for a sample of in-service primary teachers and engaged learning as a context relevant for the primary school setting. The aim was to discover the relationships between the teachers’ beliefs expressed as a rating of significance for indicators of engaged learning (EL) and performance-related self-perceptions regarding these indicators. The survey was constructed and administered for 30 primary teachers of Latvia. The content of survey is based on variable of EL developed by Jones, Valdez, Nowakowski, and Rasmussen: vision of learning, tasks, assessment, instructional model, learning context, grouping, teacher roles, student roles. Medium strength positive relationships were found between the beliefs and performance related self-perceptions of teachers. The findings suggest that beliefs regarding variable student role and assessment were more strongly linked to performance than other variables; the weakest links were found for variable tasks.